Deciding between Domains: How Borrowers Weigh Market and Interpersonal Options. (December 2022) - O'Brien, Rourke; Hayes, Adam; Kiviat, Barbara
Individuals routinely satisfy borrowing needs by transacting in the market or by relying on social relations. In the market domain, price logic leads borrowers to choose the cheaper option; in the interpersonal domain, role-matching logic leads borrowers to choose the relation best matched to the act. But how do individuals choose when faced with options from each domain? Drawing on theories in economic sociology that assert the economic and the social are mutually constitutive, we posit that when market and interpersonal options appear in the same choice set, the characteristics of one option inflect how people assess the other. Through two survey experiments, we show that price sensitivity toward the market option is less when the interpersonal option is role mismatched and that concerns about interpersonal borrowing changing or damaging the relationship attenuate when the market option is expensive. We discuss the implications for studies of stratification and financial decision-making.